Amniotic fluid stem cells: A novel treatment for necrotizing enterocolitis - Balsamo, Felicia; Tian, Yina; Pierro, Agostino; Li, Bo (Frontiers in Pediatrics, 2022)
Necrotizing enterocolitis (NEC) is a gastrointestinal disease frequently prevalent in premature neonates. Despite advances in research, there is a lack of accurate, early diagnoses of NEC and the current therapeutic approaches remain exhausted and disappointing. In this review, we have taken a close look at the regenerative medical literature available in the context of NEC treatment. Stem cells from amniotic fluid (AFSC) administration may have the greatest protective and restorative effects on NEC. This review summarizes the potential protection and restoration AFSCs have on NEC-induced intestinal injury while comparing various components within AFSCs like conditioned medium (CM) and extracellular vesicles (EVs). In addition to therapeutic interventions that focus on targeting intestinal epithelial damage and regeneration, a novel discovery that AFSCs act in a Wnt-dependent manner provides insight into this mechanism of protection. Finally, we have highlighted the most important aspects that remain unknown that should be considered to guide future research on the translational application of AFSC-based therapy. We hope that this will be a beneficial frame of reference for the guidance of future studies and towards the clinical application of AFSC and/or its derivatives as a treatment against NEC.